INTERACCIONES PREADULTAS ENTRE DROSOPHILA SIMULANS Y D. WILUSTONI (DIPTERA: DROSOPHILIDAE) EMERGIDAS DEL MISMO SUBSTRATO - Budnik, Myriam; Valente, Vera Lucía; Manríquez, Germán; Cifuentes, Lucía (Acta Entomológica Chilena, 2022)
In samples of D. willistoni and D. simulans emerging from individual fruits, the effect of larvae meta- bolic waste products on viability and egg to adult developmental time (in days) was studied. Different stocks were established with the flies emerged from individual fruits. The collections were performed in Southern Brazil. These parameters are significantly altered when larvae are bred in a culture médium where heteros- pecific preadults of different stocks of either, D. willistoni or D. simulans, have developed previously. The viability of both species was reduced and the development time of D. simulans was enlarged with the waste metabolic products of D. willistoni. The response varíes between species and between stocks within species. We discuss this finding in terms of the relative importance of such kind of interactions in the coexistence or exclusión of species in nature.